Awal Moral Kristiani - Edison R.L. Tinambunan (Litbang STFT Widya Sasana Malang, 2019)
The development of Christian morality takes a long journey which was started when the Church was born. There were many typical moral cases faced by the Church at each period of time. From one period to another one, moralists came out to solve the cases by giving the right assessment according to the Church’s way of life. A period which was well-known in the journey of Christian morality is the period of the Fathers of the Church. The principle of Christian morality is love which is based on the Gospel and the commandment of Jesus Christ. This was documented in Didache which was used by the Christians at that time. It was the principal moral document of early Christianity. In the development, it was then added by other principals: freedom and justice which were applied in the Christian life. The three principals (love, freedom and justice) formed Christian attitude in respecting other Christians and all people which is applied perfectly by Augustine. The following development of Christian morality was the development of the practice and the profound of what had been laid down before by the Fathers of the Church, with addition of the figure which is excelling in the life as Job, who had been interpreted by Gregory the Great. This writing is ended at this point, because the research is limited from the beginning up to the first development of Christian morality during the period of the Fathers of the Church.